Variability Effects Of Rainfall Events On Soil Erosion In Northernregion Of Peninsular Malaysia - Suri, Syaran (2016)
More intense rainfalls caused by climate change proven to worsen erosivity and ultimately erosion. A previous study has come up with 8R mat system that can improve slope stability and erosion control. The objectives of this study are first to obtain the trend for rainfall and climate extreme indices, second to determine the rainfall erosivity using Modified Fourneir Index and lastly to identify the relationship between rainfall intensity and the stability of 8R mat system. Four stations located in the northern region of Peninsular Malaysia were chosen. The yearly and monsoonal variations of long-term rainfall (30 years) data were studied. From the time series plot and trend analysis of mean yearly variations, Kangar provides negative significant trend indicates that Kangar will be drier. The climate extreme indices analysis shows that during southwest monsoon season, Kangar becomes drier year by year. Meanwhile, Simpang Ampat are getting wetter in northeast monsoon season. Other stations show insignificant trend of climate extreme indices. The overall studies of rainfall erosivity using Modified Fournier index show that the study area is under the moderate and low impact of rainfall erosivity. The study on erosion level using rainfall erosivity and soil erodibility at 8R mat system construction site shows that the area is under High Level 4 (HL4) level of erosion induced landslide. Finally, it is found that no significant correlations between rainfall intensity and horizontal movement of the 8R mat system. The usage of crusher run as the filling material and the construction of drain helps to prevent water from affecting the stability of this system.